Electrochemically Activated Surface Reconstruction of PdCu Nanotubes for Improved Ethanol Oxidation Electrocatalysis. Issue 6 (7th April 2022) - Fu, Qi-Qi; Li, Hui-Hui; Xu, Liang; Li, Yu-Da; Yu, Shu-Hong
Abstract : Boosting the stability of anodic electrocatalysts is of prominent importance for direct ethanol fuel cells. Precise control of the surface structure at the atomic level can effectively tune the electrocatalytic performance of materials. Here, an in situ electrochemical post‐treatment technique to rebuild a highly crystalline and stable multilayered Pd‐skin structure on Pd47 Cu53 nanotubes (NTs) via dealloying and atomic rearrangement is reported. The structural and compositional evolution of Pd47 Cu53 NTs is tracked through the whole post‐treatment process, involving sequential cyclic voltammetry (CV) and potentiostatic chronoamperometry (PC) treatments. The post‐treated Pd47 Cu53 NTs not only preserve the original tubular structure of the pristine materials, as‐prepared Pd47 Cu53 NTs, but also extensively improve the crystallinity of discrete nanoparticles (NPs) along the NTs. By comparing their catalytic performance toward ethanol oxidation reaction (EOR), the construction of a multilayered Pd‐skin surface is capable of greatly enhancing the catalytic stability of Pd47 Cu53 NTs. Such in situ electrochemical processing features and significant stabilization effects show a bright future of being a universal surface reconstruction method for alloy electrocatalysts. Abstract : A highly crystalline and stable multilayered Pd‐skin surface structure is constructed on the 3DMA Pd47 Cu53 nanotubes (NTs) by an in situ electrochemical post‐treatment technique via oxidative dealloying and atomic rearrangement. The electrochemical construction of multilayered Pd‐skin significantly enhances the catalytic performance of Pd47 Cu53 NTs toward ethanol oxidation reaction (EOR).